Influence of the Dynamically Disordered N-Terminal Tail Domain on the Amyloid Core Structure of Human Y145Stop Prion Protein Fibrils - Qi, Zhe; Surewicz, Krystyna; Surewicz, Witold K.; Jaroniec, Christopher P. (Frontiers in Molecular Biosciences, 2022)
The Y145Stop mutant of human prion protein (huPrP23-144) is associated with a familial prionopathy and provides a convenient in vitro model for investigating amyloid strains and cross-seeding barriers. huPrP23-144 fibrils feature a compact and relatively rigid parallel in-register beta-sheet amyloid core spanning ~30 C-terminal amino acid residues (~112-141) and a large ~90-residue dynamically disordered N-terminal tail domain. Here, we systematically evaluate the influence of this dynamic domain on the structure adopted by the huPrP23-144 amyloid core region, by investigating using magic-angle spinning solid-state nuclear magnetic resonance (NMR) spectroscopy a series of fibril samples formed by huPrP23-144 variants corresponding to deletions of large segments of the N-terminal tail. We find that deletion of the bulk of the N-terminal tail, up to residue 98, yields amyloid fibrils with native-like huPrP23-144 core structure. Interestingly, deletion of additional flexible residues in the stretch 99-106 located outside of the amyloid core yields shorter heterogenous fibrils with fingerprint NMR spectra that are clearly distinct from those for full-length huPrP23-144, suggestive of the onset of perturbations to the native structure and degree of molecular ordering for the core residues. For the deletion variant missing residues 99-106 we show that native huPrP23-144 core structure can be “restored” by seeding the fibril growth with preformed full-length huPrP23-144 fibrils.